Complete microbial genomes for public health in Australia and the Southwest Pacific. Issue 12 (12th December 2020) - Baines, Sarah L.; da Silva, Anders Gonçalves; Carter, Glen P.; Jennison, Amy; Rathnayake, Irani; Graham, Rikki M.; Sintchenko, Vitali; Wang, Qinning; Rockett, Rebecca J.; Timms, Verlaine J.; Martinez, Elena; Ballard, Susan; et al.
Abstract : Complete genomes of microbial pathogens are essential for the phylogenomic analyses that increasingly underpin core public health laboratory activities. Here, we announce a BioProject (PRJNA556438) dedicated to sharing complete genomes chosen to represent a range of pathogenic bacteria with regional importance to Australia and the Southwest Pacific; enriching the catalogue of globally available complete genomes for public health while providing valuable strains to regional public health microbiology laboratories. In this first step, we present 26 complete high-quality bacterial genomes. Additionally, we describe here a framework for reconstructing complete microbial genomes and highlight some of the challenges and considerations for accurate and reproducible genome reconstruction.